Pelaksanaan Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan ( PNPM MP ) ( Studi pada Desa Bendungan Kecamatan Gondang Kabupaten Tulungagung ) - Murbeng, Siaga Basu (Jurnal Administrasi Publik, 2013)
Abstract : The Implementation of Rural Community Empowerment National Program (PNPM MP). Rural development plays important role because its synergy is inseparable from the local and national developments. Many development programs have been planned by the government for the rural. Almost all offices in the local government accommodate rural development into the work program. Therefore, the objective of the research is to discuss â€œThe Implementation of PNPM MPâ€. The type of research is descriptive with qualitative approach. Second is implementation stage involving fund delivery path for PNPM Mandiri Perdesaan. Based on result of data analysis, it is concluded that Bendungan Village is relatively good for the implementation of PNPM MP. Bendungan Village has implemented PNPM MP based on the steps and empowerment method in the general guide of PNPM. This guide explains about planning, implementation and preservation stages. However, some barriers impede the implementation ofÂ  PNPM MP at Bendungan Village such as lack of understanding of PNPM MP and the quality of management, less communication with the implementing organization, and limited time for accomplishing the activity. Other less prominent barriers are less participation of citizen in the PNPM MP program and the overdue of the supply of construction material. Keywords : PNPM MP, Rural Community Empowerment, Nation building Asbtrak : Pelaksanaan Program Nasional Pemberdayaan Masyarakat Pedesaan ( PNPM MP ) Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan (PNPM Mandiri Perdesaan atau PNPM-Perdesaan atau Rural PNPM) merupakan salah satu program pemberdayaan masyarakat Â yang mendukung PNPM Mandiri yang wilayah kerja dan target sasarannya adalah masyarakat perdesaan. PNPM Mandiri Perdesaan mengadopsi sepenuhnya mekanisme dan prosedur Program Pengembangan Kecamatan (PPK) yang telah dilaksanakan sebelumnya.Penelitian ini bertujuan untuk mengetahui bagaimana pelaksanaan Program Nasional Pemberdayaan Masyarakat Mnadiri Perdesaan ( PNPM MP ) di Desa Bendungan, Kecamatan Gondang, Kabupaten Tulungagung. Penelitian ini menggunakan jenis penelitian deskriftif dengan pendekatan metode kualitatif;Dari hasil penelitian menunjukkan bahwa Pelaksanaan PNPM MP Didesa Bendungan Kecamatan Gondang. secara sistematis dibagi kedalam beberapa tahap diantaranya tahap Perencanaan kemudian Tahap Pelaksanaan dan kemudian yang terakhir ialah Tahap/proses pelestarian. Dalam pelaksanaannya PNPM MP di Desa Bendungan terdapat hambatan-hambatan diantaranya Hambatan pada pemahaman terhadap PNPM MP dan kualitas pengelola, Hambatan pada komunikasi organisasi pelaksana, Waktu pengerjaan yang dibatasi untuk setiap kegiatan Â  Kata kunci : PNPM â€“ MP, pemberdayaan masyarakat, pembangunan nasional.